Growth-climate relations and the enhancement of drought signals in pedunculate oak (Quercus robur L.) tree-ring chronology in Eastern Hungary - Árvai M (iForest - Biogeosciences and Forestry, 2018)
This paper presents an analysis of the climatic factors affecting tree-ring growth in pedunculate oak (Quercus robur L.), one of the most important species of Hungarian forests. A 221-year oak chronology was elaborated, covering the period 1789 to 2009 AD. The daily climate data for a ~110 year stretch offered a detailed insight into the climate-growth relations. The correlation function reached a maximum (r > 0.4) in the case of precipitation in May-August, providing evidence that water availability is the main factor driving the oak growth in the eastern part of the Great Hungarian Plain. Although there was no significant linear relation with temperature in the long term, moving window correlation analysis revealed that temperature response changed substantially over the course of the 20th century. While positive correlation with winter temperature was characteristic in the first decades, later the response to summer temperature strengthened remarkably, reaching r = -0.569 by the end of the analysed period (years 1978-2007). While the vulnerability of oak to drought stress is common across Europe, in southern and central Europe high summer temperatures impair tree growth. The enhanced sensitivity of pedunculate oaks to the water balance in the eastern part of the Great Hungarian Plain allows to surmise the presence of an evolving tendency towards drought risk and vulnerability in the case of these oak stands.